ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU WISATAWAN DALAM MENJAGA LINGKUNGAN OBJEK WISATA (STUDI KASUS: CANDI GEDONG SONGO) - Eka Widya NIngrum; Deden Dinar Iskandar (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2023)
The growth of tourism does not only have a positive impact such as an increase in the regional economy, but it can also cause negative externalities. One of the example is environmental damage in the tourist area. Environmental sustainability in the tourist area will be greatly influenced by the behavior of the tourists. This study aims to analyze tourists’ behavior toward the environment. This study used primary data from questionnaires distributed to the respondents who visit Candi Gedong Songo. Furthermore, this study uses multiple linear regression analysis which is Ordinary Least Squares (OLS) method. The results of the study show that attitudes, subjective norms, and perceptions of behavioral control have a positive and significant effect on intention. Intention, income, and amenities positively and significantly affect tourists’ environmentally responsible behavior. Age has a negative effect while education and personal values have no effect on tourists’ environmentally responsible behavior.Keywords: Tourist’s behavior, Theory of Planned Behavior, Environmental Responsible Behavior, Ordinary Least Squares.